1980
DOI: 10.1007/bf00441584
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid function and serum calcitonin in children receiving anticonvulsant drugs

Abstract: Serum calcitonin (CT) levels and other aspects of calcium metabolism were investigated in 40 epileptic children receiving long-term treatment with phenytoin and/or other anticonvulsant drugs, and in 38 age-matched controls. In the patients CT levels were significantly lower. Immunoreactive parathyroid hormone (iPTH) was significantly elevated exceeding the upper limit of controls in 11 patients. We also observed a highly significant correlation between iPTH and urinary cyclic AMP (cAMP) excretion but a lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
2
0
4
Order By: Relevance
“…Kruse et al [18] found low serum iCT levels in epileptic children receiving anticonvulsants. A similar observation was made for the walking patients in the present study (group 3), their serum iCT levels being slightly lower than those of the patients without therapy, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…Kruse et al [18] found low serum iCT levels in epileptic children receiving anticonvulsants. A similar observation was made for the walking patients in the present study (group 3), their serum iCT levels being slightly lower than those of the patients without therapy, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…Im Tierversuch wurde eine verminderte Ausschüttung von Calcitonin durch Phenytoingabe beobachtet (103). Kruse et al (70,71,72) untersuchten den Calcitoninspiegel bei 40 epileptischen Kindern unter antikonvulsiver Langzeittherapie und fanden diesen signifikant niedriger als in einer entsprechenden, nicht antikonvulsiv behandelten Kontrollgruppe. Die niedrigen Calcitoninspiegel waren nach den Ergebnissen der Autoren nicht auf eine Hypokalzämie zurückzuführen, sondern auf eine direkte Wirkung der Antiepileptika.…”
Section: Verminderung Der Calcitoninsekretionunclassified
“…Häufig wird bei antikonvulsiv behandelten Patienten eine Hypokalziurie gefunden (2,5,14, 28,33,50,52,70,71,72,79,94). Aladjem et al (2) yermuten einen direkten Einfluß der Antiepileptika auf die renale Calciumresorption, unabhängig vom Parathormon.…”
Section: Erhöhte Renale Calciumresorptionunclassified
See 1 more Smart Citation
“…Sugere-se também que as drogas ansiolíticas e anticonvulsivantes possam exercer efeito duplo sobre o metabolismo do osso e do cálcio, afetando não apenas o metabolismo da vitamina D, como também a ação do hormônio da paratireóide, indispensável para o remodelamento ósseo e para o desenvolvimento dentário. Esses efeitos dependem da dose e do tempo de uso desses medicamentos 19,38 . O objetivo do presente trabalho foi avaliar se o uso de Fenobarbital (Gardenal ® ) interfere na movimentação dentária induzida, comparando três grupos de animais (normal, controle e experimental) quanto ao aspecto clínico e radiográfico.…”
Section: Introductionunclassified